Rehabilitasi Jantung pada Pasien Gagal Jantung Kronik - Lumi, Axel P.; Joseph, Victor F. F.; Polii, Natalia C. I. (Jurnal Biomedik : JBM, 2021)
Abstract: Heart failure is a major clinical and public health problem with a prevalence of more than 23 million worldwide. Treatment of Heart Failure consists of pharmacological and non-pharmacological measures including physical exercise or cardiac rehabilitation. Cardiac rehabilitation is a set of integrated efforts or programs carried out to control the underlying causes of cardiovascular disease, improve physical, mental condition and as a secondary preventive measure. Cardiac rehabilitation aims to increase the patient's functional capacity, psychological adaptation to the chronic disease process, the foundation for long-term behavior and lifestyle changes to favorably influence long-term prognosis, and maintain an independent lifestyle as long as possible. The method that was used in this research is literature review by comparing the secondary data from literatures that was published in medical journal database such as PubMed, ClinicalKey and Google Scholar by following the inclusion and exclusion criteria. Reviews had been done in ten literatures that fulfill the inclusion and exclusion criteria. Those ten literature states that cardiac rehabilitation has many benefits in patients with heart failure. In conclusion, cardiac rehabilitation programs in patients with heart failure have many benefits on a patient's fitness. Cardiac rehabilitation programs can improve the quality of life in patients. The cardiac rehabilitation program increases Vo2Max and the endurance capacity of the heart. Cardiac rehabilitation program as a preventive step because it can prevent worsening heart health.Keywords: Heart failure, chronic heart failure, rehabilitationÂ Â Abstrak: Gagal jantung adalah masalah klinis dan kesehatan masyarakat yang utama dengan prevalensi lebih dari 23 juta di seluruh dunia. Penananganan Gagal Jantung terdiri dari penanganganan farmakologis dan non farmakologis yang antara lain latihan fisik atau rehabilitasi jantung. Rehabilitasi jantung adalah sekumpulan upaya atau program yang terintegrasi yang dilakukan untuk mengontrol penyebab dasar penyakit kardiovaskular, memperbaiki kondisi fisik, mental dan sebagai langkah preventif sekunder. Rehabilitasi jantung bertujuan untuk meningkatan kapasitas fungsional pasien, adaptasi psikologis terhadap proses penyakit kronis, landasan bagi perubahan perilaku dan gaya hidup jangka panjang untuk mempengaruhi prognosis jangka panjang secara menguntungkan, dan mempertahankan gaya hidup mandiri selama mungkin. Metode penelitian yang digunakan adalah literature review (studi pustaka) dengan membandingkan data sekunder dari literatur-literatur yang dipublikasi dalam database jurnal kedokteran PubMed,ClinicalKey dan Google Scholar sesuai dengan kriteria inklusi dan eksklusi yang ada. Studi pustaka dilakukan pada sepuluh literatur yang memenuhi kriteria inklusi dan eksklusi. Sepuluh literatur tersebut menyatakan bahwa rehablitasi jantung memiliki banyak manfaat pada kebugaran pasien dengan gagal jantung. Sebagai simpulan, program rehabilitasi jantung pada pasien dengan gagal jantung memiliki banyak maanfaat pada kebugaran pasien. Program rehabilitasi jantung dapat meningkatkan kualitas hidup pada pasien. Program rehabiltasi jantung meningkatkan Vo2Max dan kapasitas daya tahan jantung. Program rehabilitasi jantung sebagai langkah preventif karena dapat mencegah perburukan kesehatan jantung.Kata Kunci: Heart failure, chronic heart failure, rehabiltasi jantung